Firefox For Dummies - Ross, Blake (John Wiley & Sons, 2011)
Written by one of the inventors of Firefox, this hands-on guide will introduce you to the ins and outs of the Firefox browser, and show you how to make your online world safer, easier, and a lot more fun!